Transparent ultraviolet photodiodes based conductive gallium-indium-oxide films/p-type silicon for solar panel tracking systems - Yakuphanoğlu, F.; Gündüz B.; Al-Ghamdi A.A.; Farooq W.A.; El-Tantawy F. (Elsevier, 2015)
The conductive gallium-indium-oxide films/p-type silicon heterojunction photodiodes were prepared by sol gel method. The effects of In content (x) on rectification and photoresponse properties of the conductive gallium- indium-oxide films/p-type silicon diodes. The fabricated diodes show a rectifying non- ideal behavior. The ideality factor values obtained from dV/d(lnI) vs. I plots are higher than the ideality factor values obtained from lnI vs. V plots. This confirms that the larger n values could be due to the presence of series resistance, interface states, and the voltage drop across the interfacial layer. The capacitance values of the Al/(Ga1-xInx)2O3/p-Si/Al diode is controlled by bias voltage, frequency, illumination intensity and In content (x) value.The obtained results confirmed that conductive gallium-indium-oxide films/p-type silicon heterojunction diodes can be used as a photodiode in optoelectronic applications. ©2015 Published by Elsevier B.V.
Keywords: Photodiodes; Photosensors; Sol-gel spin coating method